Keterputusan Relasi Spasial di Kawasan Gelora Kadrie Oening: Analisis ANT terhadap Persepsi, Orientasi, dan Makna Ruang - Zulfahmiddin, Achmad Ricky; Syifa, Nikyta Na’adya; Bintang, Irgina Nur; Dian, Thesa (Universitas Mulawarman, 2025)
The Gelora Kadrie Oening (GOR Sempaja) area in Samarinda is a public space with a density of sports activities, performances, and social interactions. However, in the dynamics of the space, there is a disconnection of spatial relations between users, managers, and spatial elements such as Aji Muhammad Salehuddin II Hospital, access patterns from the main door, and post-sports consumption spaces. This research uses the Actor-Network Theory (ANT) approach to understand the connectedness and disconnectedness of human and non-human actors in the spatial structure of the area. Three main phenomena were identified: the unrecognized presence of RSUD, the shift of access from the front gate to the side lane, and the post-physical activity snacking pattern. All three were analyzed within the framework of architectural theory; sense of place, comfort theory, and spatial recognition. The findings indicate a rift in the system of perception, orientation, and spatial meaning, which hinders the overall integration of the area.